The Study of Orphism - Torjussen, Stian Sundell (Nordlit, 2005)
In this article I shall provide a brief survey of the study ofOrphism and give some indications of its present status. After a shortintroduction to the prior debate on the subject I will emphasize therole of the new material relevant to Orphism which has beenunearthed and made available to scholars since the middle of the1970s.